PEMEROLEHAN BAHASA KEDUA PADA ANAK USIA 6 DAN 7 TAHUN DI DESA BEBESEN ACEH TENGAH - Munthe, Sediken; Qurrata A’yunin; Inge Ayudia; Meli Afrodita (Lateralisasi, 2024)
This study is entitled "Second Language Acquisition in 6 and 7 Year Old Children in Bebesen Village". This study aims to describe the second language acquisition of 6 and 7 year old children and review the relationship between the environment and second language acquisition studied in the field of syntax. This study uses a qualitative descriptive method. Data were obtained from 6 year old informants named Arika Simah Bengi and 7 year old Naura Khalisa. The data collection technique used the vocative listening technique. The data obtained were analyzed based on the theory of second language acquisition. Both children use Gayo as their first language. In this case, Indonesian is their second language. The results of the study showed that some of the Indonesian sentences spoken by the informants were perfect and some were not perfect when viewed from the syntactic study. The first informant named Arika (6 years old) is already fluent in the language. However, the Indonesian used is not yet complex and the structure is still reversed. Meanwhile, the second informant named Naura (7 years old) is very fluent in Indonesian and her sentences are also complex and long.